Pegaruh Gaya Kepemimpinan, Pengawasan Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Hanesa Karya Mandiri - Rei Napeto Pasaribu; Rio Anggara Insani Sitohang; Nawarti Lumban Gaol; Holfian Daulat Tambun Saribu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of leadership style, supervision and work discipline either partially or simultaneously on the performance of employees of PT. Hanesa Karya Mandiri wholesale. This research is a descriptive study using a quantitative approach. This research is a population research with the number of respondents as many as 80 employees. The instrumentin this study has passed the stages of validity and reliability testing. Collecting data using questionnaires and interviews, while data analysis was carried out using multiple regression analysis, Test, F test and Coefficient of Determination. The classical assumption test used is the normality test, multicollinearity test and heteroscedasticity test. The results showed that Leadership Style, Supervision and Work Discipline had a positive and significant effect on employee performance at PT. Hanesa Karya Mandiri wholesale. According to the coefficient of determination test, it can be seen that 88.3% of research variables can affect the dependent variable and the remaining 11.7% are influenced by other variables outside this study. Keywords: Leadership Style, Supervision, Work Discipline, Employee Performance